Stable and metastable ferroelectric polarization analyzed by the ramp voltage technique - Wisniewski, C.; Leal Ferreira, G. F.; Faria, R. M.; Giacometti, J. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2002)
The study of the stable and the metastable ferroelectric polarization of poly(vinylidene fluoride), PVDF, was performed using two successive equal sign ramp voltages, mediated by a short-circuit period. Rates from 10 V/s up to 0.7 MV/s were used. Results showed that they follow different formation kinetics; that the stable part decreases for higher ramp voltage rates and its apparent coercive field increases.
Keywords: Coercive force; Polarization; Reaction kinetics; Vinyl resins; Metastable ferroelectric polarization; Polyvinylidene fluoride; Ramp voltage technique; Ferroelectricity